Evaluasi Sosial Ekonomi Perikanan Gurita berbasis EAFM di Wakatobi - Ode, Israwaty; Sri Wiyono, Eko; Puspitasari Sudarmo, Agnes (Jurnal Ilmu Manajemen Sosial Humaniora (JIMSH), 2025)
This study evaluates the status of Octopus cyanea fisheries management in Wakatobi Regency based on two domains of the Ecosystem Approach to Fisheries Management (EAFM): social and economic. A mixed-methods approach was employed, involving observation, in-depth interviews, and document analysis. The results indicate that the economic domain was categorized as poor (composite score: 48.33), with asset ownership, household income, and savings indicators scoring 2, 1, and 1, respectively. In contrast, the social domain was categorized as very good (composite score: 88.33), with stakeholder participation and local knowledge utilization scoring 3 (good), and fisheries conflict scoring 2 (moderate). These findings underscore the need to strengthen the economic dimension to support holistic and sustainable octopus fisheries management.